Analiza dyskursu na lekcji języka obcego - Majer, Jan (Neofilolog, 2019)
This paper outlines relevant issues in analyzing foreign language classroom communication patterns. Following a brief theoretical and historical background, it proceeds to discuss technical aspects of data collection and elaboration. Recording interaction between teachers and students is difficult but it later leads to an even more challenging task of transcribing talk. For this purpose, the article offers model instances of different traditions in compiling transcripts. However, the bulk of the present text is devoted to the exemplification of different applications of analysis of educational discourse. The samples, drawn from classroom interactions involving English, French and Polish as L2, illustrate topics such as corrective feedback, metatalk, the use of L1, and teacher questions. At the end, recommendations are given regarding further explorations and readings.